IMPLEMENTATION OF PQ4R (PREVIEW, QUESTION, READ, REFLECT, RECITE, REVIEW) LEARNING MODEL ON TEACHING AND LEARNING READING FOR TENTH YEARS STUDENTS OF SMK N 4 KLATEN - Suhud Eko Yuwono Yuwono; Kustinah kustinah; Natasya Amelia Putri Parwanta (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2023)
In achieving learning success, the learning model is the most important thing. Learning model can attract the students, it will be able to maximize learning. Thus, the writer made observations by implementing the PQ4R learning model (Preview, Question, Read, Reflect, Recite, and Review) at X AKL (Accounting) 3 SMKN 4 Klaten. Data from this qualitative research were collected from observations, interviews, tests and documentation. The results of the study are that the PQ4R learning method was successfully applied. This can be seen from the activeness of students and the score of students.